Sweet Cherries as Anti-Cancer Agents: From Bioactive Compounds to Function - Fonseca, Lara R. S. (2021)
Sweet cherries (Prunus avium L.) are among the most appreciated fruits worldwide because of their organoleptic properties and nutritional value. The accurate phytochemical composition and nutritional value of sweet cherries depends on the climatic region, cultivar, and bioaccessibility and bioavailability of specific compounds. Nevertheless, sweet cherry extracts are highly enriched in several phenolic compounds with relevant bioactivity. Over the years, technological advances in chemical analysis and fields as varied as proteomics, genomics and bioinformatics, have allowed the detailed characterization of the sweet cherry bioactive phytonutrients and their biological function. In this context, the effect of sweet cherries on suppressing important events in the carcinogenic process, such as oxidative stress and inflammation, was widely documented. Interestingly, results from our research group and others have widened the action of sweet cherries to many hallmarks of cancer, namely metabolic reprogramming. The present review discusses the anticarcinogenic potential of sweet cherries by addressing their phytochemical composition, the bioaccessibility and bioavailability of specific bioactive compounds, and the existing knowledge concerning the effects against oxidative stress, chronic inflammation, deregulated cell proliferation and apoptosis, invasion and metastization, and metabolic alterations. Globally, this review highlights the prospective use of sweet cherries as a dietary supplement or in cancer treatment.